Expression of hormone receptors and human epidermal growth Factor2/Neu in female breast cancer patients - Adrees U.; Shoaib N.; Gull S. (Kuwait Journal of Science)
Overexpression of HER2/neu and estrogen receptors (ER) and/or progesterone receptors (PR) are reported to be inversely associated with breast cancer (BC). The relationship between hormone receptors and HER2/neu is attenuated by age and numerous other clinical factors. Here, we examined the link between hormone receptors and HER-2/neu in terms of an additional variable, such as the histological grades of breast tumors in women. A total of 240 breast cancer samples were obtained from the Department of Histopathology at the University of Lahore Teaching Hospital in Lahore, Punjab. Immunohistochemistry (IHC) was used to examine the expression of hormone receptors and HER-2/neu. Using the χ2 and fisher exact test, the association between hormone receptors and HER-2/neu in various age groups and histological grades was investigated. Patients that were included in this study had ages between 30 and 90 years, with a mean age of 51.89 ± 12.01 years, and were mostly having grade 1 tumors. The most prevalent type of breast cancer was invasive ductal carcinoma (95.83%). It was found that the ER, PR, and HER-2/neu were more expressive in older (above 45) and grade 1 tumors as compared to younger (≤45) and higher-grade tumor patients. HER-2 was negatively correlated with hormonal receptors in women aged >45 years old with grade-1 tumors. Hormonal receptor (ER/PR) expression is associated with HER-2/neu expression not only in older age (>45) but also in grade 1 tumors. This correlation between HER2/neu and hormone receptors that improves with age and tumor grade is useful for predicting outcomes and, likely, for guiding therapy choices. © 2024 The Authors